2021
DOI: 10.1186/s13073-021-00827-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and functional interaction network analysis reveals global enrichment of regulatory T cell genes influencing basal cell carcinoma susceptibility

Abstract: Background Basal cell carcinoma (BCC) of the skin is the most common form of human cancer, with more than 90% of tumours presenting with clear genetic activation of the Hedgehog pathway. However, polygenic risk factors affecting mechanisms such as DNA repair and cell cycle checkpoints or which modulate the tumour microenvironment or host immune system play significant roles in determining whether genetic mutations culminate in BCC development. We set out to define background genetic factors tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…However, recent research on biological functional networks has discovered that heterogeneity can be avoided or minimized to a certain extent through the use of sequencing and bioinformatics analysis technology [ 10 14 ]. Thus, using the R language-based bioinformatics analysis technology, we designed the following research to re-evaluate the alterations in the NSCLC genome after excluding tumor heterogeneity: Based on edge perturbation [ 15 18 ], functional gene interaction networks were used to deduce the pathological environment of individual patients with NSCLC [ 19 22 ], and to identify cancer subtypes with the same or similar status, followed by a multi-dimensional and multi-omics comprehensive analysis for validation [ 23 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent research on biological functional networks has discovered that heterogeneity can be avoided or minimized to a certain extent through the use of sequencing and bioinformatics analysis technology [ 10 14 ]. Thus, using the R language-based bioinformatics analysis technology, we designed the following research to re-evaluate the alterations in the NSCLC genome after excluding tumor heterogeneity: Based on edge perturbation [ 15 18 ], functional gene interaction networks were used to deduce the pathological environment of individual patients with NSCLC [ 19 22 ], and to identify cancer subtypes with the same or similar status, followed by a multi-dimensional and multi-omics comprehensive analysis for validation [ 23 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on edge perturbation [ 15 18 ], functional gene interaction networks were used to deduce the pathological environment of NSCLC patients at the individual level [ 19 22 ], and to identify cancer subtypes with the same or similar status, followed by a multi-dimensional and multi-omics comprehensive analysis for validation [ 23 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…HLA class II , TP63, FOXP1 genes were associated with NMSC [ 68 , 69 ]. However, novel approaches that integrate skin expression-related single-nucleotide polymorphisms (eSNPs) and pathway analysis based on Kyoto Encyclopedia of Genes and Genomes (KEGG), Gene Ontology (GO), or BioCarta databases allowed identification of the role of genes of the TGF-β pathway interacting with genetic activation of the Hedgehog pathway [ 70 , 71 ]. The NO pathway in the BioCarta includes VEGFA SNPs and plays an important role in the regulation of vascular endothelial function facilitating, in particular, BCC development and an angiogenic response propagated by the growing skin cancer [ 72 ].…”
Section: Discussionmentioning
confidence: 99%
“…Deriving HEIDI test statistic is available in the Methods section of Zhu et al (2016). Recent SMR-HEIDI method-based studies have demonstrated that P HEIDI > 0.01 provides better predictions compared to the P HEIDI > 0.05 threshold defined in the original paper (Zhu et al, 2016;Wu Y. et al, 2018;Adolphe et al, 2021). Therefore, we used P HEIDI > 0.01 to exclude miRNA genes that belong to the linkage models.…”
Section: Transcriptome-wide Associationmentioning
confidence: 99%